TLUD hot air generator with forced draft - Pavel, Ioan; Matache, Gabriela; Sovaiala, Gheorghe; Popescu, Alina Iolanda; Pavel, Kati (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Energy consumption for heating and hot water in commercial and residential buildings holds a leading place in the top of the major consumer in Europe, but also in the top of the responsible for greenhouse gas emissions resulting in the atmosphere. The application of a gasification combustion technology with carbon storage in the biochar, based on the TLUD principle on environmentally friendly residential heating equipment can replace other heating systems with less environmentally friendly and less energy efficient minced biomass. The TLUD principle is recognized as the most environmentally friendly combustion process that extracts from biomass, by gasification, all volatiles (producer gas) and unconverted carbon (biochar) remains, which can be used to improve the quality of degraded soils, responding to the requirements of environmental strategies for storing carbon in the soil and reducing greenhouse gas emissions to achieve sustainable development. The article presents a hot air generator solution based on the TLUD principle and laboratory testing of the forced draft subassembly with which low speeds of the producer gas generated in the reactor (below 0.06 m/s) were obtained in order to reduce the free ash drive under the current rules imposed for solid fuel thermal generators.